2011
DOI: 10.1002/pri.529
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Hyperkyphosis: A Survey of Australian Physiotherapists

Abstract: Thoracic hyperkyphosis is commonly encountered by physiotherapists. Measurement of treatment efficacy is highly subjective, and the treatment modalities employed are diverse. Many physiotherapists based their management of hyperkyphosis on their undergraduate education alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…The development of civilization and the contemporary lifestyle are also producing a steady increase in the prevalence of postural defects [2]. Reduction in physical activity and repeatedly exceeding the body's energy needs has an adverse effect on the health and posture of the pediatric population [3]. Postural disorders are often produced by poor habits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of civilization and the contemporary lifestyle are also producing a steady increase in the prevalence of postural defects [2]. Reduction in physical activity and repeatedly exceeding the body's energy needs has an adverse effect on the health and posture of the pediatric population [3]. Postural disorders are often produced by poor habits.…”
Section: Introductionmentioning
confidence: 99%
“…Children with scoliosis have been found to demonstrate more pronounced problems with body balance, reduced response to stimuli and prolonged baseline position recovery time. Abnormal lateral spinal curvatures are particularly dangerous among postural defects; hence, the importance of early diagnosis [3]. The DIERS Formetric system is a non-invasive and objective imaging technique that may be used for assessing body posture.…”
Section: Introductionmentioning
confidence: 99%
“…16 Treatment modalities are currently in use, including surgery, bracing, and physiotherapy. 17-20 Surgery, such as balloon kyphoplasty or vertebroplasty, has been recommended for some people with acute, painful VCF, and it can reduce associated kyphosis. 21,22 However, surgery is not indicated for everyone with age-related hyperkyphosis, and there are risks, such as subsequent VCF, associated with kyphoplasty.…”
mentioning
confidence: 99%
“…Consequently, these barriers mentioned may account for the low frequency of assessment undertaken objectively by therapists in the clinical settings (Perriman et al, 2012).…”
Section: Importance Of Translation Of Research Into Clinical Practicementioning
confidence: 99%
“…Interestingly, studies demonstrated positive clinical outcomes following thoracic spine manipulation and mobilization in patients with cervical spine dysfunction (Cleland et al, 2007;Lau et al, 2011). However, its objective measurement is rarely undertaken clinically (Perriman et al, 2012), potentially because the assessment devices are timeconsuming, costly and cumbersome and are unable to provide instant feedback. Currently available tools are limited, and there is no present tool that fits the criteria of possessing high levels of both validity and reliability as well as being affordable and clinically useful by providing instant feedback and being easy to use.…”
Section: Introductionmentioning
confidence: 99%